Evaluating the knowledge of sports participants regarding dental emergency procedures in National Sports University, Imphal - Nandita Gautam; Shivalingesh KK; Anushtha Kushwaha (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Objective: To assess awareness of sports players regarding the emergency management of sports injuries in oro facial region. Methods: A self-administered, validated online questionnaire consisting of 10 questions based on knowledge of sports players regarding the emergency management of traumatized teeth was distributed among 90 (30 boxers, 30 mixed martial arts,30 Tae kwon do) players of National Sports University, Imphal. The data obtained were tabulated and statistically analyzed. Results: In our study majority of players (86.7%-96.7%) encountered trauma while playing and 70%-93% of participants among them has previous experience in managing those trauma cases. Majority of participants reported that soft tissue injuries (70%-80%) are more common than hard tissue injuries (20%-30%) while playing. Only 13% -36% participants knew that tetanus toxoid injection is necessary in dental trauma cases while 33%-60% of participants has no idea about such measure. On knowledge regarding management of these soft tissue tears 10%-33.3% reported they wipe the area neatly and apply turmeric over it, 30%-33% participants apply an ointment /dettol /spirit and 33.3%-60% prefer to visit a dentist. Only 30%-33.3% participants of our study reported to seek professional help immediately if a permanent tooth has been knocked out, and 23-26.6% reported to seek help within 30 minutes.  Conclusion: The level of knowledge, in dental emergency procedures was satisfactory among all participants. Further, rigorous training on Dental Emergency management measures need to be given.